Factores sociales que han motivado la participación de la población en el ejercicio de una ciudadanía democrática para el desarrollo comunitario en los barrios 2,3 y 3a del centro poblado alto trujillo en el año 2013. - Abanto Merejildo, Rocio Beatriz (2013)
This research was conducted in order to identify social factors that have motivated the participation of the people in the exercise of democratic citizenship in the districts 2, 3 and 3A high- Trujillo town center. It has been considered the type of descriptive research , the sample population consisted of 90 residents of the districts 2, 3 and 3A of Trujillo Alto Town Center where it has been identified that have developed participatory experiences very interesting and important to be addressed. With this study we propose to provide information to address the issue of citizen participation in sectors of the periphery , allowing to know the mechanisms of citizen participation , knowing and identifying motivates participation in places where they are present gaps and needs a view not only to research but to the application of the investigation , because as social workers seek the construction of citizenship , active participation and ongoing to improve the society in which they live, the world around them .